2018
DOI: 10.1007/s00464-018-6300-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of single-incision robotic cholecystectomy for benign gallbladder disease: a systematic review

Abstract: The use of the Da Vinci robot in single-port cholecystectomy seems to have similar results in terms of incidence and grade of complications compared to standard laparoscopy. In addition, it seems affected by the same limitations of single-port surgery, consisting of an increased operative time and incidence of port site hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Over the five years since the first robotic surgery in 1999, the robotic system has evolved to a single-site platform, enabling single-incision surgeries to be practiced in multiple departments. Initial studies have demonstrated that robotic single-site technique is safe and has potential to resolve the technical limitations of conventional laparoscopy [6]. A recent RCT described benefits of R-LESS over LESS in terms of patients' outcome and surgeons' stress load [7].…”
Section: Discussionmentioning
confidence: 99%
“…Over the five years since the first robotic surgery in 1999, the robotic system has evolved to a single-site platform, enabling single-incision surgeries to be practiced in multiple departments. Initial studies have demonstrated that robotic single-site technique is safe and has potential to resolve the technical limitations of conventional laparoscopy [6]. A recent RCT described benefits of R-LESS over LESS in terms of patients' outcome and surgeons' stress load [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that, when comparing RSSC and LSSC, RSSC is safer, easier to learn, less stressful, and technically easier for the operator to perform. 7,9,16,17 Also, other investigations have detailed that the rates of major complications and open conversion are lower in patients with high BMI compared with cases of RSSC and standard laparoscopic cholecystectomy. 18 Therefore, when comparing RSSC and SFLC in high-BMI patients, RSSC seems to be a safer procedure associated with less morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] However, SILC is not widely performed because the narrow working space limits the movement of instruments and causes crowding between instruments. [10][11][12] In 2011, the da Vinci Single-Site Instrumentation and Accessories (Intuitive Surgical, Inc., Sunnyvale, CA, USA) system was developed to overcome these limitations. 12 The semirigid instruments cross each other within the trocar, so that the cannula entering from the left becomes the right-side operative instrument and vice-versa.…”
Section: Introductionmentioning
confidence: 99%